Technical study is required for the planning and construction of a PRM warehouse and its supporting facilities, including an office and employee accommodations in Kasai Village, Batumandi District, Balangan Regency. - Hadi, Sofwan; Fajar, Reza Adhi; Ruspiansyah (Jurnal IMPACT: Implementation and Action, 2024)
In 2022, the most extensive plantation in Balangan Regency was a rubber plantation, covering an area of 37,901 hectares and producing 24,375 tons. To enhance the role and competitiveness of rubber commodities, one of the necessary efforts is to improve the quality of processed rubber materials. This requires a facility for processing, storing, and marketing rubber raw materials, whether in the form of latex, lump, slab, smoked sheet, or crepe. PT. Asabaru Dayacipta Lestari (PERSERODA), a regional company in Balangan Regency with a rubber plantation of 31,383 square meters in Batumandi District, plans to construct a warehouse for processing, storing, and marketing Processed Rubber Materials, along with office and employee accommodations. To support this, a technical study is required for the planning and construction of a PRM warehouse and its supporting facilities, including an office and employee accommodations in Kasai Village, Batumandi District, Balangan Regency. Cost analysis based on the National Building Unit Price (HSBGN) issued by the Regent includes several classifications to determine the estimated cost of physical construction, planning, supervision, and activity management. The cost estimate in this technical study is a rough estimate to be used for budgeting and as a basis for evaluating project performance. The calculation is based on the 2021 South Kalimantan Province National Building Unit Price (HSBGN), which is converted to 2024 using inflation data from the Central Statistics Agency (BPS) of South Kalimantan Province. Based on the 2021 South Kalimantan Province HSBGN for Balangan Regency, the estimated cost (budget) for the construction of a Processed Rubber Materials warehouse, office, and employee accommodations is Rp. 18,778,365,000. This cost includes estimates for planning, supervision, activity management, and construction. This estimated cost (budget) is still at an early stage and can be continued to the next stage, which is detailed planning (DED), technical specifications, and a detailed budget plan (RAB). For data accuracy, a field survey or soil testing (sounding, etc.) should be conducted. Keywords : warehouse, processed rubber materials, cost estimation